Cluster algorithms for general-S quantum spin systems - Todo, S; Kato, K (Physical review letters, 2001)
We present a general strategy to extend quantum cluster algorithms for S = 1 / 2 spin systems, such as the loop algorithm, to those with an arbitrary size of spins. The partition function of a high- S spin system is generally represented by the path integral of a S = 1 / 2 model with special boundary conditions in the imaginary-time direction. We introduce additional graphs for the boundary part and give the labeling probability explicitly, which completes the algorithm together with an existing S = 1 / 2 algorithm. As a demonstration, we simulate the integer-spin antiferromagnetic Heisenberg chains. The magnitude of the first excitation gap is estimated to be 0.41048(6), 0.08917(4), and 0.01002(3) for S = 1, 2, and 3, respectively.